Iron‐Catalyzed Synthesis of Dihydronaphthalenones from Aromatic Oxime Esters. Issue 13 (30th April 2019) - Zhang, Youcan; Yin, Zhiping; Wu, Xiao‐Feng
Abstract: Herein, a convenient procedure on iron‐catalyzed radical‐mediated synthesis of dihydronaphthalenones from oxime esters has been developed. By using iron salt as a green and inexpensive catalyst, various α‐aryl oxime esters were transformed into the corresponding dihydronaphthalenones in moderate to good yields with high chemo‐selectivities. The reaction proceeds via 1, 5‐hydrogen atom transfer and then intramolecular radical cyclization sequence. Abstract :